Quercetin inhibits cell viability, migration and invasion by regulating miR-16/HOXA10 axis in oral cancer - Zhao, Junfang; Fang, Zheng; Zha, Zhian; Sun, Qiang; Wang, Haibin; Sun, Minglei; Qiao, Bin (European journal of pharmacology, 2019)
Oral cancer is a common tumor malignancy with high mortality and poor prognosis worldwide. Quercetin is one of the major flavonoids present in our daily diet, which is reported to have anti-proliferation and apoptotic effects in varying cancers, including oral cancer. The aim of the present study is to find the mechanism that underlies the role of quercetin in oral cancer. In this study, cell viability, migration and invasion were measured by MTT, trans-well or western blot assays in oral cancer cells. The levels of microRNA-16 (miR-16) and homeobox A10 (HOXA10) were measured in oral cancer tissues and cells by quantitative real-time polymerase chain reaction (qRT-PCR). The interaction between miR-16 and HOXA10 was probed by luciferase activity, RNA immunoprecipitation (RIP) and western blot. Results showed that quercetin suppressed cell viability, migration, invasion and abundances of metalloproteinase-9 (MMP-9) and MMP-2 in oral cancer cells. miR-16 was down-regulated and reversed by addition of quercetin. Moreover, overexpression of miR-16 also impaired cell viability, migration, invasion and abundances of MMP-9 and MMP-2 in oral cancer cells. Besides, HOXA10 was targeted by miR-16 and its restoration abated miR-16-mediated role in oral cancer. In addition, knockdown of miR-16 reversed the effect of quercetin on progression of oral cancer. Collectively, quercetin inhibited cell viability, migration and invasion by regulating miR-16 and HOXA10 in oral cancer cells. This finding indicated that quercetin might be promising for treatment of oral cancer.